TABOO WORDS IN POP, ROCK, AND HIP HOP SONGS MEDAN - Riska Juli Rahmayanti and Syamsul Bahri (LINGUISTICA, 2016)
The study deals with the Taboo words uttered by the singer of pop, rock, and hip hop songs . The objective of this study was to identify the kinds and the reason of taboo words used by the songs in pop, rock, and hip hop genres. The source of the data was lyrics of three lates album in recent five years (2010-2015) which lead three genres; Miley Cyrus for pop, Linkin Park for rock, and Nicki Minaj for hip hop. Each of singers brought five songs as the data. The data were collected by selecting lyrics containing taboo words after listening the song and matching the lyrics from internet carefully. The results of this study were four kinds of taboo words; offensive slang, profanity, sexual referent, and scatological referent occured in the songs and the most dominant kinds of taboo word appeared was offensive slang.